Author's reply [to comments on 'A proposal to improve the accuracy of linguistic modelling']. - Cordon, O. (IEEE Transactions on fuzzy systems)
In our opinion, there are two main concerns in Roubos and Babugka's note, that are summarized as follows. 1) The kinds of problems used in our paper to test the algorithm proposed in "A proposal to improve the accuracy of linguistic modeling" and other studies. The authors claim that they are very simple to be considered as benchmarks for nonlinear modeling techniques. 2) The interpretability of the different kinds of models considered. Roubos and Babuska think that there is no difference between the interpretability of fuzzy linguistic models, Takagi-Sugeno-Kang (TSK) fuzzy models, and mathematical formulations (linear models, in this case). We agree with some of the opinions of the authors of the note but not with some others.